Development of a Sport Science and Tactical Training-Based Coaching Model for Football Coaches in Aceh Province - septi hariansyah; Zulheri Is (CV Abid Abadi Jaya, 2026)
This community service program aimed to improve football coaches’ competencies through sport science and tactical training–based coaching in Aceh Province. The main problems faced by participants included limited understanding of modern training methods, scientific training program design, and tactical training implementation. The program employed a participatory approach consisting of needs analysis, module development, material delivery, field practice, mentoring, and evaluation. Participants included 30 football coaches from soccer schools, local clubs, and football academies in Aceh. Training materials covered sport science, training periodization, physical conditioning management, small-sided games, performance analysis, and tactical training. The results showed significant improvement in participants’ competencies, with average understanding increasing from 62% before training to 86% after training. Participants also demonstrated better skills in designing training programs and managing game-based training sessions. Therefore, the sport science and tactical training model proved effective in enhancing football coaching quality and supporting sustainable sports development in Aceh Province